Nida`s Dynamic equivalence theory : Applied to selected translations of Mahfouz`s Trilogy - Asmaa Amr Abdelfatah Mohamed Ashour; Mohamed Yehia Mohamed Hasan (Cairo : Asmaa Amr Abdelfatah Mohamed Ashour, 2010)
The present thesis attempts a study of the problms of translating literary work as exemplified by selected excerpts from Naguib Mahfouz`s Trilogy in the light of Eugene Nida`s theory of dynamic equivalence . The Trilogy consists of Palace Walk, Palace of Desire and Sugar Street . This study envisages using a comparative analytical approach . The present study shows how Nida`s dynamic equivalence theory is useful in solving the literary problems as manifested by translated examples from Mahfouz`s Trilogy
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Dynamic equivalence; Modern standard Arabic; Naguib Mahfouz`s